The e+e− → Zγγ → qq ̄γγ reaction at LEP and constraints on anomalous quartic gauge boson couplings - Dova, María Teresa (2002)
The cross section of the process e+e− → Zγ γ → qq ̄γ γ is measured with 215 pb−1 of data collected with the L3 detector during the final LEP run at centre-of-mass energies around 205 GeV and 207 GeV. No deviation from the Standard Model expectation is observed. The full data sample of 713 pb−1, collected above the Z resonance, is used to constrain the coefficients of anomalous quartic gauge boson couplings to: −0.02 GeV−2 < a0/Λ2 < 0.03 GeV−2, −0.07 GeV−2 < ac/Λ2 < 0.05 GeV−2, at 95% confidence level.